ПРОЕКТИ ВИЩОЇ ПЕДАГОГІЧНОЇ ОСВІТИ В УКРАЇНІ ПЕРШОЇ ПОЛОВИНИ ХІХ ст. (World Science, 2020)
The period of the first half of the nineteenth century is characterized by a significant number of the pedagogical education projects development, which can be divided into two main groups: the author’s (M. Demkov, V. Ivanovsky, G. Kollontay, M. Pirogov, М. Troitsky, K. Ushinsky, T.Chacky, etc.) and official (authorized by the Ministry of Public Education). Among them are the projects of Pedagogical Institute in the "Prior Rules of Public Education" (1803), the General Regulations of the Russian Imperial Universities in 1804 and 1835, the Pedagogical Courses Principles (1860, 1865); the draft of the Teaching Institute Regulations (1862) and a number of others. It`s considered that author's approaches significantly influenced the content of the official group and even served as their basis.The analysis of the projects content is allowed to group them into two divisions. The first is the projects of educational institutions for the primary school teachers training (teachers' seminary, teacher's institutes), and the second one is educational institutions for the secondary school teachers training (pedagogical faculties, pedagogical institutes, pedagogical courses, pedagogical seminaries). At the same time, the first projects were planned as an independent, exclusively closed educational institutions of the residential type. Their curricula had to provide the detailed learning of the primary schools disciplines and the teaching methods. A compulsory condition for the existence of the second group was their opening on the basis of universities, which according to the authors of the projects had to provide a broad compulsory education and special training for advanced teaching. The dominant for university teaching institutions was the viewpoint of their open type, which is slightly allowed to reduce the cost of teacher training, providing teacher applicants with scholarships rather than complete public funds.The common requirement for both types of projects was the requirement for compulsory in-depth pedagogical training, which, as a rule, reflected the need to follow the principle of theoretical pedagogical courses unity (pedagogy, didactics, knowledge about upbringing, history of pedagogical currents, etc.) and pedagogical training.Thereby the pedagogical institute on this basis was opened in the structure of the University of St. Volodymyr in Kyiv in 1834. Having passed the difficult historical path, today is known in the world educational space by a large-scale innovative activity as National Pedagogical Dragomanov University, it is still the custodian of the university pedagogical institute idea of the 1830s, traditions of teacher training.